Managing future air quality in megacities: Emission inventory and scenario analysis for the Kolkata Metropolitan City, India. (1st February 2020) - Majumdar, Dipanjali; Purohit, Pallav; Bhanarkar, Anil D.; Rao, Padma S.; Rafaj, Peter; Amann, Markus; Sander, Robert; Pakrashi, Ankita; Srivastava, Anjali
Abstract: Air pollution in Indian cities is a serious problem and a threat to human health. Kolkata Metropolitan City (KMC) is one of the Indian metro cities urgently requiring policy interventions to ensure breathable air in the near future. We developed a detailed emissions inventory of key air pollutants for 2015 in KMC, considering both particulate matter (PM10, PM2.5, BC, OC) and gaseous pollutants (SO2, NOx, CO, VOC and NH3 ). We estimated the emissions in a business-as-usual (BAU) scenario for the year 2030, while accounting for the impacts of current and planned policies. Our results reveal that current policies/measures are not sufficient to reduce PM2.5 emissions substantially in KMC by 2030. We thus explored three alternative policy scenarios considering various emission control strategies and non-technical city-specific control measures, along with associated cost implications. Our results indicate that significant emission reductions can be achieved (35% for PM2.5 and 45% for NOx) by spending €1.15 billion for advanced control measures across various sectors, compared with the business-as-usual scenario, are expected to cost €0.78 billion by 2030. Advanced control measures, coupled with the control of non-technical emission sources, may prove to be the most effective solution, yielding a significant reduction of key air pollutants (51% for PM2.5 and 54% for NOx) with a cost implication of €1.18 billion by 2030. Low carbon policies may also be able to substantially reduce key air pollutants with the additional co-benefit of reduced emissions of greenhouse gas, CO2 by 24% in 2030, with a running cost of €0.70 billion. Highlights: We develop an emissions inventory of air pollutants and greenhouse gases for Kolkata, India. The GAINS-City model is used to analyze future emission scenarios for Kolkata. Current policies are not sufficient to substantially reduce PM2.5 emissions by 2030. City-specific measures will be required for sufficient emission reductions.